القيمة الإنذارية لمستوى كولسترول المصل في تقدير شـدة قصور الخلية الكبدية - انطانيوس ميلاد; زيزفون حسان; أسعد علي (Latakia University Journal -Medical Sciences Series, 2019)
مقدمة: إن الكبد يعتبر الموقع الأكثر أهمية في استقلاب الكولسترول والبروتينات الشحمية، لذلك تم دراسة مستويات كولسترول المصل في آفات الكبد ودورها في تحديد الإنذار [1]. مواد وطرق البحث: تم معايرة الكولسترول الكلي وLDL عند 50 مريض تشمع كبد (25 ذكراً و25 أنثى، متوسط أعمارهم 54.39 ± 9.3 سنة). وتم تصنيفهم حسب تشايلد المعدل إلى:8 ينتمي إلى المجموعة A، 23 ينتمي إلى المجموعة B، 19 ينتمي إلى المجموعة C، وعند 16 مريضاً التهاب كبد حاد (9 رجال و7 إناث، متوسط أعمارهم 31.41 ± 6.27)، ثم تم ربط الموجودات بشدة الداء الكبدي (تصنيف تشايلد المعَّدل). النتائج: عند مرضى التشمع كان هناك انخفاضاً واضحاً في قيم الكولسترول الكلي، والكولسترول LDL وهذا الانخفاض يتناسب طرداً مع تقدم شدة الداء الكبدي بدءً من A إلى C. عند مرضى التهاب الكبد الحاد: الكولسترول الكلي طبيعي ماعدا عند مرضى التهاب الكبد الخاطف كان منخفضاً جداً. الخلاصة: الانخفاض الشديد في مستويات الكولسترول خاصة الكولسترول LDL عند مرضى التشمع يرتبط بشدة تطور الداء الكبدي، وبالتالي فإن الانخفاض في مستويات الكولسترول الكلي وLDL هام في المعالجة الفعالة وتحديد القيمة الإنذارية عند مرضى الداء الكبدي المزمن. Back ground: The liver is the most active site of cholesterol and lipoprotein metabolism, so that we evaluated the effects of the liver diseases on serum cholesterol level, and its role in prognostic value [1]. Methods and material: We measured cholesterol and LDL in 50 patients with liver cirrhosis (25 men and 25 women, their age average 54.39 ± 9.3 years). Modified child classes: 8 in A, 23 in B, 19 in C. and in 16 patients with a cute hepatitis (9 mean, 7 women, mean age 31.41 ± 6.27 years). We relate the findings to the severity of the cirrhosis. Results: In patients, with cirrhosis there was a significant decrease in cholesterol and in LDL, and these were progressively lower compared to the intensity of the liver in fection starting from A to C, while in patients with Acutehepatitis, cholesterol was normal, except in fulminante hepatitis was very low. Conclusions: In this study the striking decrease in cholesterol and LDL in patients with cirrhosis was related to the increasing severity of the disease. Accordingly the assessment of cholesterol and LDL is important for an effective treatment and prognostic evaluation of patient with chronic liver disease.